Norges Bank's BEER Models for the Norwegian Effective Exchange Rate - Kjetil Martinsen (Norges Bank, 2017)
I revisit Norges Bank's Behavioural Equilibrium Exchange Rate (BEER) models for the Norwegian effective exchange rate first introduced in Flatner et al. (2010) and extend the model framework in several directions. Two medium-term BEER models are estimated using both short- and long-term interest rate differentials, where the latter intends to capture the effects of unconventional monetary policy. Both models include the oil price, relative consumer prices and a measure for the Norwegian "basic balance", an approximation of Mainland Norway's current account. Moreover, the short-term BEER model is extended with a long-term interest rate differential and a measure of Norwegian specific foreign exchange volatility. I show that the movements in the effective exchange rate can be explained quite well by the fundamental explanatory variables in the model framework.
hdl:11250/2506374
Keywords: 330